Transcriptomic Analysis of the Regulation of Lipid Fraction Migration and Fatty Acid Biosynthesis in Schizochytrium sp. - Lujing Ren (Nature Portfolio, 2017)
Abstract Schizochytrium sp. is the main source of docosahexaenoic acid-rich oil, which is widely used in food additive and pharmaceutical industry. In this study, using RNA-seq, comparative transcriptomic analyses were performed at four stages of DHA fermentation by Schizochytrium sp to get potential genes related to cell transition from cell growth to lipid accumulation and then to lipid turnover. 1406, 385, 1384 differently expressed genes were identified by comparisons in pairs of S2 vs S1, S3 vs S2 and S4 vs S3. Functional analysis revealed that binding and single-organism process might be involve in the cell transition from cell growth to lipid accumulation while oxidation-reduction process played an important role in the transition from lipid accumulation to lipid turnover. pfaC in the PKS pathway showed higher sensitivity to the environmental change, which might be the key regulator for enhancing PUFA biosynthesis in the future. Some other genes in signal transduction and cell transport were revealed to be related to lipid turnover, which would enrich the current knowledge regarding lipid metabolism and help to enhance the DHA production and enrich different lipid fractions by Schizochytrium in the future.